Politik Hukum Pasca Putusan Mahkamah Konstitusi atas Pelaksanaan Pemilu dan Pemilukada di Indonesia - Nugroho, Wahyu (Mahkamah Konstitusi Republik Indonesia, 2016)
After amendment 1945, whether legislative elections and the election of the executive power implementing held directly by the people, and going political reform electoral laws and local election, both in the revision of the existing political regulations, and rules in the law after the Constitutional Court decision, namely Law No. 42 of 2008 on General Election of President and Vice President, and and Law No. 10 of 2016 on the Second Amendment of Act No. 1 of 2015 on Stipulation of Government Regulation in Lieu of Law No. 1 of 2014 on the election of Governors, Regents and Mayors became acts. The purpose of the study on the implementation of the legal political and local elections are to conduct political rearrangement and local elections law in a mosaic of Indonesian state structure, maturity in politics, the consolidation of local democracy, and changes in local people’s minds to develop the region very hung to the figure of its leader, as well as ensuring the political rights of citizens in national and local political constellation. The results in this study is the need for consistency of law enforcement for compliance with a number of legal instruments and the implementation of procedures and penalties in the administration of elections. Aspects of legal certainty and the cultural aspect is very important law met in order for the elections and the local election purpose in achieving this goal idealized.In addition, the electoral administration in central and local levels, as well as participating in the election and the election shall comply with laws and regulations, ranging from the Commission Regulation, Act, as well as adherence to Constitutional Court decision. The author draws conclusions that the renewal of electoral politics and the local election after the Constitutional Court Decision in the Indonesian constitutional structure has implications for changes in the system, the mechanism and the pattern of elections and the local election organizers and participants of the election and the local election. On some empirical experience that was shown in the administration of elections and the election, people think the dynamic to organize and improve the system, as well as have awareness of constitutional rights guaranteed by the 1945 Constitution on political rights for the sake of the spirit of building area through the local elections to choose a figure that is idealized.